Innovations in Nipple-areolar Complex Reconstruction: Evaluation of a New Prosthesis - Michele Riccio, MD; Angelica Aquinati, MD; Mario Fordellone, PhD; Nicola Carboni, MD; Andrea Marchesini, MD; Francesco De Francesco, MD, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. The reconstruction of the nipple-areola complex (NAC) is a crucial step for completing breast restoration with patient satisfaction. Surgical reconstruction or tattooing of the NAC may not be preferable or feasible for some patients. There is no universal method for NAC that is ideal for every patient or clinical situation. Various approaches often do not maintain projection over time. Over time, several techniques have been perfected, including the C-V flap, to improve and support projection for patients with bilateral implant-based reconstructions. Methods:. We used, for the first time, prosthetic devices for NAC reconstruction and examined the safety of these devices associated with ease of implantation and patient satisfaction levels using a survey conducted during a 1-year follow-up. We enrolled 20 individuals who opted for these NAC prostheses following unilateral or bilateral breast reconstruction and following NAC excision. Results:. Ninety percent of the participants expressed satisfaction or high satisfaction with the appearance and balance of the new NAC. The prosthetics enhanced the overall body self-image and self-regard of all the study participants. Except for 4 patients, there were no reports of skin adverse reactions, infections, or erosion. Conclusions:. Encouraged by these auspicious outcomes that indicate a significant rate of safety and satisfaction, we believe that this straightforward, noninvasive, affordable medical device deserves consideration as a reconstructive option for all patients seeking breast reconstruction, promoting full body integrity.